Indigenous Peoples Leadership Capacity Building Program For The Andean Countries - Rodas, Jorge E. Uquillas (World Bank, Washington, DC, 2012)
The Indigenous Peoples Leadership Capacity Building Program for the Andean Countries (Andean Program) is the result of an initiative of the Fund for the Development of Indigenous Peoples of Latin America and the Caribbean (Fondo Indígena), supported initially by the governments of Ecuador and Peru and later by the main national indigenous organizations of the Andean countries of Bolivia, Colombia, Ecuador, Peru and Venezuela. Responding to this interest, the World Bank started a participatory process to identify the demand and the most important themes which would be the basis for a capacity-building program. As a consequence, training modules on governance, development with identity, indigenous rights, and the use of technologies of information and communications (ICT) have been prepared and validated in a series of workshops held since 2003, with the participation of indigenous leaders.